Struktur Tari Bubu di Sanggar Tari Putri Kelana Kabupaten Penukal Abab Lematang Ilir (PALI) - Sumantri, Pino; Rochayati, Rully; Hasan, Hasan (ANTHOR: Education and Learning Journal, 2022)
Abstract Bubu Dance is a new creation dance in Putri Kelana Dance Studio, Penukal Abab Lematang Ilir Regency, created in 2018. The problem formulation in this study is "How is the Bubu Tariff Structure in Putri Kelana Dance Studio, Penukal Abab Lematang Ilir Regency". The purpose of this study was to determine the structure of the dance which includes motion motifs, motion phrases, motion sentences, and movement groups. Qualitative descriptiveresearch method that involves observation. The interview data obtained include the questions posed by obtaining more complete data, while the documentation is in the form of photos. The results of the analysis of the data obtained are a comparison of the Bubu dance consisting of 3 movement groups, 23 motion sentences, 42 movement phrases, and 87 movement motifs. In Bubu dance, one movement motif and the next are intertwined to form a movement sentence, and the next phrase forms a movement sentence and the next sentence forms a movement group. The basic element of dance is that the body is divided into four parts, namely the head,posture, hands, and feet, each part is divided into two, namely the elements of posture and elements of motion. the head consists of 6 elements of posture and 3 elements of movement, the hands consist of 9 elements of posture and 7 movements, the feet consist of 8 elements ofposture and 6 elements of movement and the body consists of 6 elements of posture and 4 elements of movement.